1980
DOI: 10.1126/science.7384792
|View full text |Cite
|
Sign up to set email alerts
|

Swim Bladder Volume Maintenance Related to Initial Oceanic Migratory Depth in Silver-Phase Anguilla rostrata

Abstract: Gas deposition rates in the swim bladders of postmetamorphic (silver) Anguilla rostrata eels are about five times greater than those of premetamorphic (yellow) individuals. This extends the maximum depth at which silver eels can maintain swim bladder volume and prepares them for their spawning migration to the Sargasso Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 2 publications
1
50
0
1
Order By: Relevance
“…Artificially matured Anguilla anguilla released in the Sargasso Sea did not descend beyond 300 m (Fricke & Kaese 1995), while partially matured A. japonica swam at mean depths ranging from 81 to 172 m (Aoyama et al 1999b). Experimental evidence from maintenance of swimbladder volume (Kleckner 1980) and temperatures required for gonad maturation (Boetius & Boetius 1967) are also consistent with migration and spawning within 200 m of the surface. Although depth was not recorded during the present study, the fact that light levels could be recorded on most days indicated that eels remained within the euphotic zone, at least during daylight hours.…”
Section: Swimming Depthmentioning
confidence: 73%
“…Artificially matured Anguilla anguilla released in the Sargasso Sea did not descend beyond 300 m (Fricke & Kaese 1995), while partially matured A. japonica swam at mean depths ranging from 81 to 172 m (Aoyama et al 1999b). Experimental evidence from maintenance of swimbladder volume (Kleckner 1980) and temperatures required for gonad maturation (Boetius & Boetius 1967) are also consistent with migration and spawning within 200 m of the surface. Although depth was not recorded during the present study, the fact that light levels could be recorded on most days indicated that eels remained within the euphotic zone, at least during daylight hours.…”
Section: Swimming Depthmentioning
confidence: 73%
“…Ce stade est non seulement caractérisé par un changement de couleur de la peau mais aussi par des modifications au niveau de la musculature (PANKHURST, 1982b), du tractus digestif (SORENSEN et PANKHURST, 1988), des branchies (FONTAINE et al, 1995), de la vessie natatoire (KLECKNER, 1980 ;KLECKNER et KRUEGER, 1981), des organes sensoriels (PANKHURST, 1982a ;PANKHURST et LYTHGOE, 1983) et des gonades (FONTAINE, 1989 ;FONTAINE et DUFOUR, 1991 ;DUFOUR, 1994). Cette métamorphose qu'est l'argenture se mettrait en place pour des tailles corporelles moyennes supérieures à 35 cm chez les mâles et à 45 cm chez les femelles (pour revue : LECOMTE-FINIGER, 1990).…”
Section: Key-wordsunclassified
“…These changes are thought to be adaptations for their oceanic spawning migration (Kleckner, 1980;Pankhurst and Lythgoe, 1982;Pankhurst and Lythgoe, 1983;Tsukamoto, 2009). However, not all eels that migrate downstream show the obvious external characteristics of silver eels (Vøllestad et al, 1986;Haro, 2003;Winter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%